A multiscale and Trefftz computational method for medium-frequency vibrations of assemblies of heterogeneous plates - Blanc, L.; Blanzé, C.; Ladevèze, P.; Rouch, P. (Computer Assisted Methods in Engineering and Science, 2023)
A new approach called the "Variational Theory of Complex Rays" has been developed in order to calculate the vibrations of slightly damped elastic plates in the medium-frequency range. The solution of a small system of equations, which does not result from a fine spatial discretization of the structure, leads to the evaluation of effective quantities (deformation energy, vibration amplitude, ... ). Here we extend this approach, which was already validated for assemblies of homogeneous substructures, to the case of heterogeneous substructures.